2021
DOI: 10.1039/d1ra01678d
|View full text |Cite
|
Sign up to set email alerts
|

A nanostructured SnO2/Ni/CNT composite as an anode for Li ion batteries

Abstract: SnO2/Ni/CNT nanocomposite approach has been demonstrated which confers shielding against volume expansion due to the use of optimum % of Ni & CNT exhibiting superior cycling stability and rate capabilities of the stable electrode structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The peaks at around 1.31 and 1.92 V are caused by the oxidation of Sn to SnO and SnO 2 . , It can be found that there is no obvious peak about Ni in the CV curve of SNC, which is due to the low content of Ni in SNC, thus leading to the inconspicuous oxidation and reduction peaks and the overlap with SnO 2 . The CV curves of SNC can be found to be significantly different from the CV curves of SC (Figure C) and SnO 2 (Figure E), including the position of the redox peaks and the areas enclosed by the CV curves; this is also the reason for the difference in the electrochemical performance of the three. , In addition, the CV curves of the second and third cycles of SNC almost overlap, while the CV curves of SC and SnO 2 overlap lesser, indicating that Ni doping and CNT wrapping can enhance the material reversibility and greatly improve the electrochemical performance. , …”
Section: Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The peaks at around 1.31 and 1.92 V are caused by the oxidation of Sn to SnO and SnO 2 . , It can be found that there is no obvious peak about Ni in the CV curve of SNC, which is due to the low content of Ni in SNC, thus leading to the inconspicuous oxidation and reduction peaks and the overlap with SnO 2 . The CV curves of SNC can be found to be significantly different from the CV curves of SC (Figure C) and SnO 2 (Figure E), including the position of the redox peaks and the areas enclosed by the CV curves; this is also the reason for the difference in the electrochemical performance of the three. , In addition, the CV curves of the second and third cycles of SNC almost overlap, while the CV curves of SC and SnO 2 overlap lesser, indicating that Ni doping and CNT wrapping can enhance the material reversibility and greatly improve the electrochemical performance. , …”
Section: Results and Discussionmentioning
confidence: 94%
“…The CV curves of SNC can be found to be significantly different from the CV curves of SC (Figure 5C) and SnO 2 (Figure 5E), including the position of the redox peaks and the areas enclosed by the CV curves; this is also the reason for the difference in the electrochemical performance of the three. 26,41 In addition, the CV curves of the second and third cycles of SNC almost overlap, while the CV curves of SC and SnO 2 overlap lesser, indicating that Ni doping and CNT wrapping can enhance the material reversibility and greatly improve the electrochemical performance. 39,42 The charge and discharge curves can also be used to describe the electrochemical reaction process of SNC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the safety concern and the low capacity (372 mAh g −1 ) of commercial graphite material impeded its application in high-energy LIBs. Therefore, researchers are facing to develop the low cost, efficient, eco-friendly, small size and light weight electrical energy storage devices as one of the major challenges they confronted [2]. Transition metal oxides (TMOs, usually 400-900 mAh g -1 ) have got a lot of attention, because of easy preparation, low cost, large energy density, and good safety [3].…”
Section: Introductionmentioning
confidence: 99%